2021
DOI: 10.1038/s41598-021-96139-4
|View full text |Cite
|
Sign up to set email alerts
|

Gait change in tongue movement

Abstract: During locomotion, humans switch gaits from walking to running, and horses from walking to trotting to cantering to galloping, as they increase their movement rate. It is unknown whether gait change leading to a wider movement rate range is limited to locomotive-type behaviours, or instead is a general property of any rate-varying motor system. The tongue during speech provides a motor system that can address this gap. In controlled speech experiments, using phrases containing complex tongue-movement sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Donald Derrick 1 and Bryan Gick 2,3 1 University of Canterbury, Christchurch, New Zealand 2 University of British Columbia, Vancouver, Canada 3 Haskins Laboratories, New Haven, CT, United States of America In a recent paper (Derrick & Gick, 2021), we demonstrated that gait change leading to wider movement rate ranges, analogous to switching from walking to running, occurs in the tongue during speech. North American English (NAE) speakers were recorded producing phrases with /VRVRV/ sequences with rhotic and non-rhotic vowels; results showed speakers who have a wide speech rate also categorically switch tongue motion patterns between slow and fast speech.…”
Section: Gait Change In Tongue Movement In American and New Zealand E...mentioning
confidence: 98%
“…Donald Derrick 1 and Bryan Gick 2,3 1 University of Canterbury, Christchurch, New Zealand 2 University of British Columbia, Vancouver, Canada 3 Haskins Laboratories, New Haven, CT, United States of America In a recent paper (Derrick & Gick, 2021), we demonstrated that gait change leading to wider movement rate ranges, analogous to switching from walking to running, occurs in the tongue during speech. North American English (NAE) speakers were recorded producing phrases with /VRVRV/ sequences with rhotic and non-rhotic vowels; results showed speakers who have a wide speech rate also categorically switch tongue motion patterns between slow and fast speech.…”
Section: Gait Change In Tongue Movement In American and New Zealand E...mentioning
confidence: 98%